2008
DOI: 10.1029/2008ja013610
|View full text |Cite
|
Sign up to set email alerts
|

The dawn‐dusk asymmetry of energetic electron in the Earth's magnetotail: Observation and transport models

Abstract: [1] We have studied the dawn-dusk asymmetry of the energetic/thermal particle in the plasma sheet using the Geotail data. We found the species-and energy-dependent dawndusk asymmetries in the plasma sheet. The dawn-dusk asymmetries have some typical structures, and we used a finite width two-dimensional model of the magnetotail to explain their characteristics. The characteristics and assumptions of our model can be summarized as follows: (1) the magnetotail convection is steady (both of magnetic field and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Despite sparse measurements, it is possible to distinguish a dawn‐dusk asymmetry in Figures 6b and 6d, where there is a tendency for energetic electron fluxes to be higher on the dawn side of the plasma sheet. Bame et al [1967] and Imada et al [2008], among others, found a dawn‐dusk asymmetry in the plasma sheet, with energetic electrons having higher fluxes on the dawn side. This may be due to electrons drifting eastward and filling the dawn side more than dusk [ Korth et al , 1999].…”
Section: Discussionmentioning
confidence: 92%
“…Despite sparse measurements, it is possible to distinguish a dawn‐dusk asymmetry in Figures 6b and 6d, where there is a tendency for energetic electron fluxes to be higher on the dawn side of the plasma sheet. Bame et al [1967] and Imada et al [2008], among others, found a dawn‐dusk asymmetry in the plasma sheet, with energetic electrons having higher fluxes on the dawn side. This may be due to electrons drifting eastward and filling the dawn side more than dusk [ Korth et al , 1999].…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, BBFs have a strong capability to transport energetic electrons to the Earth. Usually without BBFs, plasma sheet energetic electrons more easily escape from the dawnward flank of the magnetotail [ Imada et al ., ].…”
Section: Observationsmentioning
confidence: 99%
“…Moreover, Cassini's extremely fast (9 Re per hour) transverse survey in the distant magnetosheath gave us a global picture of the energetic particles as well as the state‐of‐art level energy resolution in the medium‐energy range (>10 keV). Considering the dawn‐dusk asymmetry in the plasma sheet [e.g., Meng et al , 1981; Imada et al , 2008], the Cassini swing‐by trajectory in the dawnside magnetosheath will be advantageous to discover especially for electrons of magnetosphere origin under the constant dusk‐ward electric field in the terrestrial plasma sheet. Thanks to the recent multisatellite missions, in addition to the simple models of the magnetospheric particle leakage via particle drift and/or the magnetic field reconnection at the magnetopause, the energization process [ Dunlop et al , 2008] and the mixture of the particles of magnetospheric and solar wind origin via substructures [ Hasegawa et al , 2004] at the LLBL are attracting a lot of attention.…”
Section: Introductionmentioning
confidence: 99%